Dynamic regulation of canonical TGFβ signalling by endothelial transcription factor ERG protects from liver fibrogenesis - Neil P. Dufton (Nature Portfolio, 2017)
The transcription factor ERG is key to endothelial lineage specification and vascular homeostasis. Here the authors show that ERG balances TGFβ signalling through the SMAD1 and SMAD3 pathways, protecting the endothelium from endothelial-to-mesenchymal transition and consequent liver fibrosis in mice via a SMAD3-dependent mechanism.